PREDICTORS OF NEUROTIC DISORDERS IN ADOLESCENTS - Proskurina, T.Yu. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The paper presents an analysis of prognostic factors as regards neurotic disorders in adolescents. There have been systematized certain specific and unspecific factors of psychological traumatizing in neurasthenia and in neurotic depressive and anxiety-phobic disturbances in adolescents. Principal trends of medical-socio-psychological support for the adolescents with neurotic disorders have been established.